Do soil microbes regulate citrus fruit quality through soil nutrient availability? - Tang, Dou; Zhou, Yuzhou; Cui, Haojie; Liao, Wenjuan; Liu, Pei; Zhou, Weijun; Nie, Sanan (Frontiers in Plant Science, 2026)
The relationship between soil microbes and citrus fruit quality is not fully understood at the moment. In this study, we collected citrus fruit and soil samples from fifteen orchards with generally similar planting conditions and soil profiles. Fruits were categorized into three quality types, namely, SL (small-weight and low Vitamin C), SH (small-weight and high Vitamin C), and BH (big-weight and high Vitamin C), respectively, based on PCA analysis. The results indicated significant differences (P < 0.05) were observed in the relative abundances of Acidobacteriia, Deltaproteobacteria, and Tremellomycetes at class level. Bacterial α-diversity showed no significant differences, whereas fungal communities exhibited significant differences in Shannon and Simpson index. Significant differences in β-diversity were observed among the groups. Microbial co-occurrence network analysis revealed a higher proportion of positive correlations in the BH group, suggesting stronger microbial cooperation. Redundancy analysis (RDA) demonstrated that fruit weight was influenced by soil pH, organic matter, and alkali-hydrolysable nitrogen as well as fungal Shannon and Simpson indices. Soil microbial taxa and available phosphorus significantly affected fruit quality indicators such as Vitamin C (Vc) content, titratable acidity, and soluble solids content. We propose that the diversity, composition, and co-occurrence networks of soil microbiota collectively influence soil nutrient availability. This nutrient availability, in turn, acts as a key determinant of citrus fruit quality.